Effect of a Four-Week Vegan Diet on Performance, Training Efficiency and Blood Biochemical Indices in CrossFit-Trained Participants - Durkalec-Michalski, Krzysztof; Domagalski, Adrian; Główka, Natalia; Kamińska, Joanna; Szymczak, Damian; Podgórski, Tomasz (Nutrients, 2022)
This interventional study examined the effect of a four-week vegan diet (VegD) during a four-week high-intensity functional training (HIFT) on performance, training results and blood biochemical indices in female (n = 12) and male (n = 8) moderate-trained CrossFit participants. The whole study group performed the maximum number of repetitions with a load of 70% one repetition-maximum (1RM) and a modified Fight Gone Bad (FGBMod) test before and after a dietary intervention (the group was divided to follow a VegD or a traditional mixed diet (MixD)) in a randomised and parallel design. Pre-exercise resting blood samples were also analysed. There was a significant improvement in the number of repetitions performed at a load corresponding to 70% of 1RM in the classic squat in the MixD group (p < 0.001), and in the classic deadlift in the VegD group (p = 0.014). Furthermore, there was a significant improvement in the results of the FGBMod performance test after a MixD. Moreover, an improvement in some exercises in the modified FGBMod test (Wall Ball after the VegD and the MixD, and rowing after the MixD) was also observed. However, differences between the MixD and the VegD groups were not clinically relevant. In conclusion, the short-term study conducted here indicated that a VegD in HIFT training positively affects strength endurance in the classic deadlift but is unlikely to be more beneficial in improving performance than a MixD.
Keywords: Humans; svalová síla; odporový trénink; Exercise; dieta veganská; Muscle Strength; Muscle, Skeletal; kosterní svaly; mužské pohlaví; cvičení; Resistance Training; Diet, Vegan; lidé; ženské pohlaví; Female; Male